2018
DOI: 10.3389/fphys.2018.00900
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Brain Axis, the Human Gut Microbiota and Their Integration in the Development of Obesity

Abstract: Obesity is a global epidemic, placing socioeconomic strain on public healthcare systems, especially within the so-called Western countries, such as Australia, United States, United Kingdom, and Canada. Obesity results from an imbalance between energy intake and energy expenditure, where energy intake exceeds expenditure. Current non-invasive treatments lack efficacy in combating obesity, suggesting that obesity is a multi-faceted and more complex disease than previously thought. This has led to an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 304 publications
0
105
0
5
Order By: Relevance
“…Notably, SCFAs always act on the GPRs, FFAR2 and FFAR3 to induce the release of gut peptides (GLP‐1 and PYY) (Lin et al . 2012; Bliss and Whiteside 2018). Our results also showed that the mRNA expressions of SCFA receptor GPR41 and GPR43 increased, suggesting that SCFAs are greatly utilized by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SCFAs always act on the GPRs, FFAR2 and FFAR3 to induce the release of gut peptides (GLP‐1 and PYY) (Lin et al . 2012; Bliss and Whiteside 2018). Our results also showed that the mRNA expressions of SCFA receptor GPR41 and GPR43 increased, suggesting that SCFAs are greatly utilized by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Connecting pathways include gut hormone signaling to modulate appetite and gut motility, tryptophan metabolism and vagal nerve signaling, as well as SCFA effects on several tissues including adipose tissue to regulate the secretion of cytokines with central regulatory effects. The gut microbiome has moreover been suggested to influence behavior including feeding but also enteric inflammation leading to obesity, all of which have been reviewed in detail elsewhere [187]. The gut microbiome has proven essential for the development of the enteric nervous system by regulation of serotonin production and tryptophan metabolism as well as modulating 5-HT4R-specific signaling.…”
Section: Brain and Nervous Systemmentioning
confidence: 99%
“…tion of several hormones [46]. These gut microbiota-derived metabolites can modulate the nervous network through afferent nerves and gut hormone secretion including peptide YY (PYY), glucagon like peptide-1 (GLP-1), and cholecystokinin (CCK) [46,47]. The gut microbiota-producing SCFAs can also modulate appetite and food intake via the gut-brain axis.…”
Section: Gut-brain Axis: Modulation Of Appetitementioning
confidence: 99%